Comparative Study of the Anticoagulant Activity of Zingiber Officinale and Curcuma longa Rhizomes Extracts in Blood Samples of Normal Individuals - Albara Ahmad, Safaa Jafar Mohammed, Ikram Mohamed Eltayeb, Yousif Mohammed Elmosaad, Hisham Ali Waggiallah, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The current study compares the anticoagulant activity of curcumin and ginger rhizome extracts in vitro. Background: Curcuma longa and Zingiber officinale (Ginger) (turmeric, curcuma, or curcumin) Rhizomes are widely used as a spice and in herbal medicine around the world. Methods: To obtain the entire crude extract, Zingiber officinale and Curcuma longa rhizomes were pulverized and extracted in 70% ethanol. The phytochemical contents of the extracts were determined. Their anticoagulant impact was tested in vitro on blood samples from healthy Sudanese people by assessing prothrombin time (PT) and activated partial thromboplastin time (APTT). Results: The ginger extract inhibited coagulation and significantly prolonged prothrombin time (PT) in a dose-dependent manner (25,50, 75 μl) with P. value 0.001, whereas APTT showed insignificant prolongation (P. value 0.139). PT and APTT of curcumin showed insignificant prolongation among (25, 50, 75μl) with P. value 0.55 and 0.146, respectively. Conclusion: The in vitro anticoagulant effect demonstrated that ginger and curcumin extracts had equal anticoagulant activity, but curcumin has a higher anticoagulant impact with considerable PT prolongation.